2007
DOI: 10.1200/jco.2006.08.9987
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Aromatherapy Massage in the Management of Anxiety and Depression in Patients With Cancer: A Multicenter Randomized Controlled Trial

Abstract: Aromatherapy massage does not appear to confer benefit on cancer patients' anxiety and/or depression in the long-term, but is associated with clinically important benefit up to 2 weeks after the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
136
1
21

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(165 citation statements)
references
References 24 publications
7
136
1
21
Order By: Relevance
“…The effect sizes for outcomes reported in a trial of problem-solving therapy trial [42], comparing problem-solving therapy to a wait-list control (Hedges's g = 3.76) or problem-solving therapy with a significant other to the wait-list control (Hedges's g = 4.30) were exceedingly large. The effect sizes on 2 outcome measures from aromatherapy with massage [45] were small (Hedges's g = 0.17 to 0.22) and not statistically significant. Effect sizes for each individual study are shown in Table 1.…”
Section: Review Question #1: Effect Of Treatment Of Psychological Dismentioning
confidence: 99%
See 3 more Smart Citations
“…The effect sizes for outcomes reported in a trial of problem-solving therapy trial [42], comparing problem-solving therapy to a wait-list control (Hedges's g = 3.76) or problem-solving therapy with a significant other to the wait-list control (Hedges's g = 4.30) were exceedingly large. The effect sizes on 2 outcome measures from aromatherapy with massage [45] were small (Hedges's g = 0.17 to 0.22) and not statistically significant. Effect sizes for each individual study are shown in Table 1.…”
Section: Review Question #1: Effect Of Treatment Of Psychological Dismentioning
confidence: 99%
“…The other 10 studies included collaborative care interventions [35,37,40,44,46], cognitive behavior therapy [36,39,41], problem solving therapy [42], and aromatherapy massage [45]. Among the drug trials, there was 1 study [38] with at least 64 patients per group, and that study found a small effect size reduction on self-reported depressive symptoms with fluoxetine (Hedges's g = 0.23).…”
Section: Review Question #1: Effect Of Treatment Of Psychological Dismentioning
confidence: 99%
See 2 more Smart Citations
“…Massage is often combined with aromatherapy, and beneficial effects have been reported previously (52). research designed to evaluate the relative contributions of the extra physical and social contact would be of considerable interest, especially in light of this study's findings.…”
Section: Discussionmentioning
confidence: 99%